Pengaruh Kreativitas dan Motivasi Kerja terhadap Produktivitas Guru Pendidikan Agama Islam Sekolah Menengah Atas Sekecamatan Talo Kabupaten Seluma - Abdul Aziz, Faisal (GHAITSA : Islamic Education Journal, 2020)
The purposes of this study are: (1) to determine the influence of creativity and productivity of Islamic Education (PAI) teachers of all Senior High Schools in district Talo, Seluma of 2018/2019 (2) to determine the influence between work motivation and productivity of Islamic Education (PAI) teachers of all Senior High Schools in district Talo, Seluma of 2018/2019 (3) to determine the influence of creativity and work motivation and productivity of Islamic Education (PAI) teachers of all Senior High Schools in district Talo Seluma of 2018/2019. This research was conducted at all Senior High Schools of Talo, Seluma districts consisted of 6 schools. The method used in this study was a quantitative correlation. Methods of data collection used a questionnaire. The conclusions of this study are (1) There is an influence between creativity and productivity of Islamic Education (PAI) teachers of all Senior High Schools in district Talo. (2) There is an influence between work motivation and productivity of Islamic Education (PAI) teachers of all Senior High Schools in district Talo. (3) There is an influence between creativity and work motivation as well as productivity of Islamic Education (PAI) teachers of all Senior High Schools in district Talo.